Diagnóstico educacional: uma avaliação do município de Autazes no período de 2010 a 2020 - Leão, Maria do Carmo da Silveira (Brasil, 2024)
Assuming that human capital, determined by education, has a significant impact on the economic performance of a population, boosting economic progress, it can be assumed that regions that have a higher level of education will consequently have a greater probability of growth and prosperity, on the other hand, regions characterized by educational deficiency or lower than average levels tend to economic stagnation. The general objective of this research is to carry out an educational diagnosis of the municipality of Autazes from 2010 to 2020. It consists of quantitative and descriptive research. Data collection took place through educational indicators calculated, mainly, by the School Census carried out by INEP. The results obtained indicate that the municipality of Autazes, with regard to educational deficit, improvement in the quality of teaching and performance, presents the majority of results below the comparison parameters, accompanied by an evolution trend similar to the state averages. Over the period between 2010 and 2020, the municipality generally reflected a significant improvement in the educational system. However, despite this, some indicators point to certain points of deficiency that reveal the need for improvement in the current situation of education in Autazes.